Muhammadiyah’s Paradigm of Progressive Islamic Education: A Philosophical Analysis of the Concepts of Tajdid and Social Transformation - Mukmin Mukmin; Ade Adriani; Muslimin Muslimin; Ruslan Ruslan (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the paradigm of Muhammadiyah's progressive Islamic education from a philosophical perspective, analyze the concept of tajdid in Muhammadiyah education as a foundation for social transformation, and identify the relevance of the paradigm of Muhammadiyah's progressive Islamic education in facing educational challenges in the era of disruption and modernization. The study uses a qualitative approach with library research. Data sources are obtained from official Muhammadiyah documents, works of Muhammadiyah figures, books, and scientific journal articles relevant to Islamic education, tajdid, and social transformation. Data analysis is carried out using content analysis techniques and a philosophical hermeneutic approach to understand the ontological, epistemological, and axiological constructions of Muhammadiyah's progressive Islamic education paradigm. The results show that Muhammadiyah's progressive Islamic education is an educational paradigm that integrates the values of monotheism, science, modernity, and orientation to social change in a holistic educational system. The concept of tajdid is not only interpreted as a purification of Islamic teachings, but also a renewal of thought and an educational system that is adaptive to the development of the times. This paradigm is relevant in addressing contemporary educational challenges such as technological disruption, moral crisis, and globalization through strengthening digital literacy, religious moderation, and developing a progressive and humanistic Islamic character. Thus, Muhammadiyah's progressive Islamic education is a model of contemporary Islamic education that is transformative, inclusive, and oriented toward the advancement of civilization.